AKTIVITAS BIOSURFAKTAN KALDU FERMENTASI ISOLAT WNA 4.1.13 ASAL SEDIMEN MANGROVE WONOREJO SURABAYA DAN POTENSINYA SEBAGAI ANTIJAMUR Candida albicans ATCC 10231 - CATUR RAHAYUNINGSIH, 061511133078 (2019)
The aim of this research was to identify the genus of WNA 4.1.13 that produced biosurfactant and its potential as antifungal to Candida albicans ATCC 10231. WNA 4.1.13 was isolated from mangrove sediment in Wonorejo Surabaya. Isolate was identified by observing the character of colony and cell morphology. Gram and spora stain was used to identify cells morphology. Biosurfactant activities were tested with drop collapse test, oil spreading test and parafilm test. Antifungal activities was tested using well diffusion method. The results showed that WNA 4.1.13 from mangrove sediment in Wonorejo Surabaya was bacil, Gram positive, and having endospore in the center of the cell. The genus of WNA 4.1.13 determined as Bacillus sp based on character of colony and cell morphology. The result also showed that fermented broth droplets was flat on the drop collapse test, forming a clear zone on the oil spreading test and increasing of the diameter on parafilm test. The antifungal activity was showing a inhibition zone that produced by WNA 4.1.13 fermented broth was 37.12 mm, 23.60 mm produced by ketoconazole 0.005% and 6.28 mm produced by MSM. The conclution were WNA 4.1.13 fermented broth from mangrove sediment in Wonorejo Surabaya has biosurfactant activity and has potential as antifungal to Candida albicans ATCC 10231. Keywords : Biosurfactant, antifungal, mangrove, Candida albicans, fermented broth.